Enhancing Ecosystem Harmonization Understanding Interactive Flipbook Media in Science for Grade V : Flipbook Learning Media Based on Problem Solving - Dwindahari, I Dw Ayu Arika Resma; I Gede Astawan (Universitas Pendidikan Ganesha, 2025)
In today's educational context, students often struggle to grasp complex concepts such as ecosystem harmonization due to the use of conventional teaching methods. This issue calls for innovative and engaging learning media to promote deeper understanding and enhance problem-solving skills. This study aims to develop a problem-solving-based flipbook learning media for the topic of ecosystem harmonization in fifth-grade elementary science education. This developmental research employs the ADDIE model, with a research sample consisting of 30 fifth-grade students. Data collection methods include questionnaires and tests. Data were analyzed using quantitative descriptive techniques and inferential statistical analysis through a t-test. The results showed that the flipbook learning media is feasible and effective, as evidenced by: (1) a design expert score of 92.05% (very good), (2) a learning material expert score of 80.35% (good), and (3) significant effectiveness test results (tvalue = 16.286 > ttable = 2.045, p < 0.05). Thus, it can be concluded that the problem-solving-based flipbook is an appropriate and effective tool for improving students’ understanding of ecosystem harmonization in science learning. This research implies the potential to enhance the effectiveness of science education in elementary schools by strengthening students' critical thinking and problem-solving skills.